Interim C-reactive protein levels predict the prognosis of patients with metastatic colorectal cancer receiving immunotherapy: a retrospective cohort study - Hai-Yan Fu; Yi-Yang Zhang; Jin-Shan Huang; Jin-Xin Hu; Kun-Hao Bai; Zhi-Qiang Wang (Therapeutic Advances in Medical Oncology)
Background: Serum C-reactive protein (CRP) level is frequently considered a prognostic predictor of immunotherapy. However, the prognostic role of the interim serum CRP levels before the third course of immunotherapy (CRP-C3) in patients with metastatic colorectal cancer (mCRC) receiving immunotherapy remains unclear. Objectives: This study aimed to determine the predictive value of CRP-C3 for immunotherapy response and progression-free survival (PFS) and to compare its performance with other biomarkers, such as tumor mutational burden (TMB). Design: We conducted a retrospective cohort study of 205 patients with mCRC who received immunotherapy. Methods: Baseline CRP (CRP-B) and CRP-C3 levels were measured in this retrospective cohort study. Clinicopathological data were retrospectively analyzed using Cox regression analyses to identify independent predictive variables for immunotherapy response and PFS, then summarized in nomograms to predict prognosis. Results: The median PFS periods were 8.47 months in the CRP-C3-low subgroup and 2.47 months in the CRP-C3-high subgroup ( p  < 0.001). The objective response rate (ORR) was 40.6% and 8.9%, respectively ( p  < 0.001). Although CRP-B failed in the multivariate Cox analysis, CRP-C3 performed exceptionally well, surpassing TMB levels (both p  < 0.001). Moreover, a prognostic model combining CRP-C3 and TMB levels could significantly stratify patients with mCRC receiving immunotherapy into low-, intermediate-, and high-risk subgroups ( p  < 0.001). Patients from different risk subgroups exhibited significantly different ORR (low- vs intermediate- vs high-risk groups: 59.2% vs 32.5% vs 0%, respectively, p  < 0.001) and Kaplan–Meier survival curves ( p  < 0.001). Conclusion: This retrospective study indicates a potential association between decreased CRP-C3 levels and improved PFS in patients with mCRC receiving immunotherapy. The combination of CRP-C3 and TMB appeared to enhance predictive performance, suggesting their possible utility as prognostic indicators.